Pleurodesis After Bronchial Occlusion for Inoperable Secondary Spontaneous Pneumothorax. Issue 4 (October 2021) - Kida, Hirotaka; Muraoka, Hiromi; Morikawa, Kei; Inoue, Takeo; Mineshita, Masamichi
Abstract : Background: In many cases of secondary spontaneous pneumothorax (SSP), surgery is not feasible. Furthermore, in cases with a collapsed lung or numerous air leaks, pleurodesis is ineffective, and treatment options are severely limited. For these cases, bronchial occlusion might be the only effective treatment, despite the low success rate. If, however, bronchial occlusion can expand the lung and reduce air leakage, it can positively amplify later effects on pleurodesis, resulting in a powerful treatment. We reviewed the clinical data of patients who underwent bronchial occlusion with endobronchial Watanabe spigot (BO-EWS) and pleurodesis to investigate the usefulness of bronchial occlusion therapy in inoperable SSP patients. Materials and Methods: This single-center, retrospective study reviewed 36 cases of inoperable SSP patients who underwent pleurodesis after BO-EWS from April 2007 to October 2018. Twenty cases were allocated to the air leak analysis group, and 16 cases were included in the pneumothorax volume analysis group. The Robert David Cerfolio classification and the Collins method were used to evaluate air leak and pneumothorax volume, respectively. Results: Pneumothorax volumes decreased significantly after BO-EWS from 29.1%±17.3% to 12.1%±8.8%, while the air leak score decreased from 2.9±1.4 to 1.2±1.0. The success rate for chest tube removals in cases that underwent pleurodesis after BO-EWS was 85.0% (17/20). Conclusions: This study demonstrated the synergistic effectiveness of BO-EWS and the usefulness of pleurodesis treatment in inoperable SSP patients with lung collapse or numerous air leaks. We believe that this treatment will benefit patients with inoperable SSP which, until now, has had few treatment options.